Electron-Induced Reactions of Ru(CO)4I2: Gas Phase, Surface, and Electron Beam-Induced Deposition - Thorman, Rachel M; Jensen, Pernille A; Yu, Jo-Chi; Matsuda, Scott J; McElwee-White, Lisa; Ingólfsson, Oddur; Fairbrother, D. Howard (Journal of physical chemistry. C, 2020)
The reactions of low energy (<100 eV) electrons with organometallic precursors underpin the fabrication of metal-containing nanostructures using focused electron beam-induced deposition. To understand these reactions at a molecular level, we have studied the electron-induced reactions of Ru(CO)4I2 in three different environments: as isolated molecules in the gas phase, adsorbed as thin films on surfaces, and as used in electron beam-induced deposition (EBID) in an Auger spectrometer. Gas-phase studies show that dissociative electron attachment (DEA) to Ru(CO)4I2 predominantly results in the loss of two CO ligands, while dissociative ionization (DI) of Ru(CO)4I2 leads to significantly more extensive fragmentation. Surface science studies of thin films of Ru(CO)4I2 adsorbed on gold at −100 °C and irradiated with 500 eV electrons show that decomposition proceeds in two distinct steps: (1) an initial loss of two CO ligands, followed by (2) a slower step, where the residual two CO ligands desorb, leaving RuI2 on the surface. EBID using Ru(CO)4I2 and its brominated analogue, Ru(CO)4Br2, produced deposits with a ruthenium-to-halide ratio of ≈1:2 and minimal carbon and oxygen contamination. These results suggest that DEA is dominant over DI in the initial deposition step on the surface. This step produces a partially decarbonylated Ru(CO)2I2 species, which is then subject to CO desorption under further electron irradiation, findings likely generalizable to other Ru(CO)4X2 species (X = halide). The desorption of CO from the partially decarbonylated intermediate differs markedly from the results obtained for other metal carbonyls (e.g., W(CO)6), a difference tentatively ascribed to the presence of M–X bonds.